EcoHealth Enterprise / Muhammad Syaza Iman Muzafek...[et.al] - Othman, Mohamad Syafizal; Mohd Shah, Mohamad Shahrul Izwan; Fauzi, Mohd Fadli; Mad Johari, Ainun Jariah; Hamid, Muhammad Sadiq (Faculty of Plantation and Agrotechnology, 2016)
First of all our company was named EcoHealth Enterprise. The establishment of EcoHealth Enterprise was on 13th July 2016. Our company was based on partnership. The partnership agreement has been formed on 13th July of 2016, No 32, at Malacca between the shareholders that have listed down.